BHÂLÂ-MOSO: RELASI SOSIAL MASYARAKAT MADURA DALAM KUMPULAN CERPEN KARAPAN LAUT KARYA MAHWI AIR TAWAR - Rozekki, Rozekki (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2018)
Abstract This research aims to yield the social relation of Madura society in the anthology of short story Karapan Laut by Mahwi Air Tawar, covering (1) social relation of bhâlâ (companion), and (2) social relation of moso (opponent). Base on the purpose can be concluded the followings: (1) bhâlâ divided to become two, bhâlâ mata (only in vision) and bhâlâ atè (really companion), and (2) moso also divided two, moso dâlâm (relative) and moso lowar (others), besides, moso can be divided again become moso mata (visible) and moso atè (unvisible), also there is moso salaje (unilateral) and moso dukalaje (bilateral).